Translations of the Runic Inscriptions at Maeshowe, Orkney (Proceedings of the Society of Antiquaries of Scotland, 1864)
A notice of John M Mitchell's publication on the runic inscriptions titled 'Mesehowe: Illustrations of the Runic Literature of Scandinavia, Translations in Danish and English of the Inscriptions in Mesehowe, Visits of the Northern Sovereigns to Orkney, Notes, Vocabulary, &c'.